The association and aggregation of the metamorphic chemokine lymphotactin with fondaparinux: from nm molecular complexes to μm molecular assemblies. Issue 2 (2nd November 2015) - Harvey, Sophie R.; MacPhee, Cait E.; Volkman, Brian F.; Barran, Perdita E.
Abstract : Transmission electron microscopy and drift tube ion mobility-mass spectrometry are used to study the assemblies formed by the metamorphic chemokine lymphotactin in the presence of a model glycosaminoglycan. Abstract : Transmission electron microscopy, mass spectrometry, and drift tube ion mobility-mass spectrometry are used to study the assemblies formed by the metamorphic chemokine lymphotactin in the presence of a model pentameric glycosaminoglycan, fondaparinux. This combination of techniques delineates significant differences in the complexes observed for two forms of the full length protein as well as a truncated form, without the intrinsically disordered C-terminal tail, over a length scale from few nm to μm assemblies.